2023
DOI: 10.52312/jdrs.2023.1280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different internal fixation implants in the treatment of talar neck fractures: A finite element analysis

Xin Fu,
Hong-Bin Cao,
Nan Li
et al.

Abstract: Objectives This study aimed to analyze the biomechanics of cannulated screws (CS) with or without a lateral locking plate (LLP) in talar neck fractures through a finite element analysis. Patients and methods The computed tomography image of the talus from a healthy volunteer (adult male) was used to reconstruct a three-dimensional talar model. The method for fixing talar neck fractures with CS and an LLP was planned using computer-aided design software. Afterward, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In managing complex central talar fractures, a strategy involving miniaturized plates combined with screws can be employed. A finite element analysis demonstrated that the dual medial cannulated screws (CS) with a lateral locking plate (LLP) in comminuted talar neck fractures had better biomechanics properties in the displacement and stress peak of the talus and implant compared to dual CS and single CS with LLP 28 . Biomechanical research suggests that plates offer superior resistance to rotation and shear compared to using screws alone 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In managing complex central talar fractures, a strategy involving miniaturized plates combined with screws can be employed. A finite element analysis demonstrated that the dual medial cannulated screws (CS) with a lateral locking plate (LLP) in comminuted talar neck fractures had better biomechanics properties in the displacement and stress peak of the talus and implant compared to dual CS and single CS with LLP 28 . Biomechanical research suggests that plates offer superior resistance to rotation and shear compared to using screws alone 13 …”
Section: Discussionmentioning
confidence: 99%
“…A finite element analysis demonstrated that the dual medial cannulated screws (CS) with a lateral locking plate (LLP) in comminuted talar neck fractures had better biomechanics properties in the displacement and stress peak of the talus and implant compared to dual CS and single CS with LLP. 28 Biomechanical research suggests that plates offer superior resistance to rotation and shear compared to using screws alone. 13 Isolated talar neck fractures usually present with comminution of the dorsal and medial aspect of the neck of the talus, however, the comminution of complex central talar fracture may be on the medial and/or lateral.…”
Section: Internal Fixation Strategymentioning
confidence: 99%